Changing Pattern of Childhood Celiac Disease Epidemiology: Contributing Factors - Popp, Alina; Mäki, Markku (Frontiers in Pediatrics, 2019)
In the 1960’s and earlier, diarrhea, malabsorption syndrome and failure to thrive were the presenting symptoms and signs of celiac disease (CD) in young infants and this disease was reported to be disappearing. It became clear the clinical picture of childhood CD changed to milder forms resulting in an upward shift of age at diagnosis in the 1970’s and in some countries this happened years and decades later. The changing pattern of CD altered the epidemiology of the disease, high differences between countries and within countries were observed. The awareness of changing clinics and use of case finding tools became an important factor in the changing epidemiology. Low and high prevalence countries exist but the overall prevalence is on the increase and approximately 1-2%. We discuss the potential reasons, the environmental factors for the observed clinical changes and found new clues in publications from the time when the actual changing pattern took place. Breast feeding postponed the diagnosis of the disease, it did not prevent it. Time of gluten introduction, when started very early, at the mean age of 2 months, seemed to have a clear impact, same for the gluten amount and type of cereals in the weaning food. The impact of cow’s milk and its osmolarity might be difficult to estimate today, because of the humanized milk formulas used today. Future epidemiological studies on environmental factors contributing to the disease should take place in countries where the changing clinical features are still forthcoming.